Clinical outcomes in overweight heart transplant recipients - Jalowiec, Anne (Heart Lung, 2016)
BACKGROUND: There is a paucity of research examining the impact of patient weight after heart transplant (HT) on multiple clinical outcomes. OBJECTIVES: The purpose of this study was to compare 9 clinical outcomes in 2 groups of HT recipients (N = 347) from 2 hospitals in the midwestern and southern United States, based on their mean body mass index (BMI) during the first 3 years post-HT, and to identify risk factors for mortality. METHODS: The sample was divided into 2 groups: Group 1: 108 non-overweight patients (BMI <25; mean age 52; 29.6% females; 16.7% minorities), and Group 2: 239 overweight patients (BMI ≥25; mean age 52; 15.9% females; 13.8% minorities). Outcomes examined were: survival, re-hospitalization, rejections, infections, cardiac allograft vasculopathy (CAV), stroke, renal dysfunction, diabetes, and lymphoma. RESULTS: Non-overweight patients had shorter survival, were re-hospitalized more days after the HT discharge, and had more lymphoma and severe renal dysfunction. Overweight patients had more CAV, steroid-induced diabetes, and acute rejections. Mortality risk factors were: higher prednisone dose, higher cholesterol, earlier IV-treated infection, severe renal dysfunction, respiratory failure, and female patient. CONCLUSIONS: Overweight HT patients had better survival, but more rejections, CAV, and diabetes. Non-overweight HT patients had worse survival, plus more re-hospitalization time, lymphoma, and renal dysfunction.